2018
DOI: 10.4103/ijoem.ijoem_63_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of silicosis awareness among stone mine workers of Rajasthan state

Abstract: Background:Silicosis is a known occupational lung disease prevalent among stone mine workers. It is commonly characterized by cough and shortening of breath, and is occasionally associated with tuberculosis and lung carcinogenicity. Silicosis is one of the major occupational disease all over the world and poses detrimental health effects to the workers in developing countries like India.Objective:The present study was conducted to assess the level of awareness and knowledge of silicosis among stone mine worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Unfortunately, limited research has been conducted on silica dust health hazard awareness in developing countries unlike in the developed world (Falk et al, 2019;Nandi et al, 2018;Sayler et al, 2018;Seaton et al, 1991;Sivanmani & Rajathinakar, 2013). It is important silica exposed workers have adequate knowledge about the health hazards silica dust exposure can cause.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, limited research has been conducted on silica dust health hazard awareness in developing countries unlike in the developed world (Falk et al, 2019;Nandi et al, 2018;Sayler et al, 2018;Seaton et al, 1991;Sivanmani & Rajathinakar, 2013). It is important silica exposed workers have adequate knowledge about the health hazards silica dust exposure can cause.…”
Section: Introductionmentioning
confidence: 99%
“…Since the recent increase in mining, current estimates are unavailable for the number of mine workers in Iran. However, past estimates claim that in Iran, more than 8000 workers are exposed to mineral and silica dust [1]; while in the United States, 1.7 million are exposed to crystalline silica [4,5]. The American Conference of Governmental Industrial Hygienists (ACGIH) and the Occupational Health Committee of Iran have both declared 10 mg/m 3 and 3 mg/m 3 as threshold limits for an 8-hour workday exposure to total dust and respirable dust, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of these methods is also dependent on how they are used and/or maintained by workers, which in turn is associated with the knowledge, attitudes and behaviour of workers in workplaces [ 55 , 56 ]. A range of studies in different countries such as Vietnam [ 57 ], India [ 58 , 59 ], Spain [ 60 ], and China [ 61 ] consistently demonstrated that educated workers who are given adequate information and training were likely to be aware of the harmful outcomes of occupational exposure to silica dust [ 56 ], and therefore more willing to comply with health standards and regulations [ 62 , 63 ]. Moreover, educating workers has a direct impact on their proper use of prevention practices such as the effective use of personal protective respiratory equipment, which may prevent worsening of pulmonary function due to reduced dust exposure [ 64 ].…”
Section: The Hostmentioning
confidence: 99%